Pencegahan Stanting dalam Perspektif Maqashid asy-Syariah: Studi Kasus di Bansari Kabupaten Temanggung - Ifadah , Luluk; Nur Afnan , Achmad (El-Qenon: Journal of Islamic Law, 2024)
The high stunting rate of toddlers in Indonesia is a reflection of chronic malnutrition which requires seriousness from all parties in preventing it as a concrete form of protecting children's rights in their growth and development. Stunting prevention is part of the process of safeguarding the Muslim generation as stated in Maqashid Asy Syari'ah which is specifically carried out in Purborejo Village. This research is a qualitative research with a phenomenological approach with a type of field research. The data sources used in this research are primary data sources in the form of observations and interviews and secondary data sources in the form of documentation results. Furthermore, data collection techniques use the open observation method, semi-structured interview method, and documentation method. Meanwhile, data triangulation uses method triangulation and data source triangulation. The results of this research state that stunting prevention strategies by increasing public awareness through posyandu, posbindu, humanist approaches are used to reduce community apathy towards stunted children. The stunting task force collaborates with Islamic religious instructors and preachers to socialize stunting through religious language based on Maqashid asy syari'ah. The Maqashid asyari'ah perspective aims to optimize the physical, mental and intelligent conditions of children as the next generation of religion and nation, maintaining the soul, mind and offspring in good and optimal conditions.